Influência da Disbiose na Patologia do Couro Cabeludo - Francisca Morgado; Rui Oliveira Soares (Sociedade Portuguesa de Dermatologia e Venereologia, 2021)
In recent years, several studies have demonstrated the involvement of the intestinal microbiota in immune-mediated diseases such as diabetes, ulcerative colitis, and multiple sclerosis. There are few data on the follicular microbiome and its role in the pathogenesis of scalp diseases. Some studies show influence of dysbiosis on these diseases, and manipulation of the microbiome may represent a possible therapeu- tic option. This article reviews current knowledge regarding the impact of dysbiosis on dermatological diseases of the scalp, such as seborrheic dermatitis, psoriasis, alopecia areata, androgenetic alopecia, lichen planus pilaris, frontal fibrosing alopecia and decalvant folliculitis. A broader understanding of this may suggest additional treatments beyond conventional therapies.